The Six Minute Walk Test as a Marker of Functional Capacity in Hypertensive Patients - Sidhi Laksono Purwowiyoto; Steven Philip Surya (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Currently, hypertension becomes one of the leading issues not only for medical community but also to the broader societies. Even though hypertension could be symptomatic, in most case it didn’t until the devastating complications shows up. Functional capacity is a simple tool based on our daily activity. The six-minute walk test could be one of the simplest ways in measuring functional capacity. Six-minute distance as the outcome of this test could be potentially a marker for functional capacity in hypertensive group compare to non-hypertensive group.Methods: This is a case control study with 34 female participants in six-minute walking test.Result: There are no significant different of age, height, weight, and body max index between those groups. The six-minute walking distance drastically difference between hypertensive and non-hypertensive group, 306m and 367m respectively with p-value < 0,01. Heart rate pre-test also statistically different between control group and case group. (75 bpm and 94 bpm, p-value = 0,027) Post-test blood pressure is notably distinctive between two groups. Additionally, systolic blood pressure post-test lower than initial value. Hypertension alters human functional capacity ominously.Conclusion : The six-minute walk test could be applied as simple functional capacity marker in hypertension subject.